Analisis Asas Pemungutan Pajak di Indonesia dalam Perspektif Maqashid Syariah - Aip Wahidzul Latif; Roifatus Syauqoti (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2026)
This study aims to analyze the principles of tax collection in Indonesia from the perspective of Maqashid Syariah to understand the compatibility between modern tax principles and the objectives of public welfare in Islamic law. The study uses a qualitative approach with a library study design and conceptual analysis. Data were collected through documentation of tax laws and regulations, fiscal policy documents, Maqashid Syariah literature, and national and international scientific articles published in the 2020–2025 period. Data validity was strengthened through source triangulation and audit trails, while data analysis used the Miles and Huberman interactive model which includes data condensation, data presentation, and conclusion drawing. The results of the study indicate that the principles of justice, legal certainty, benefit, and efficiency that form the basis of tax collection in Indonesia have substantive compatibility with the objectives of Maqashid Syariah, particularly in the protection of property (hifz al-mal), life (hifz al-nafs), intellect (hifz al-'aql), and descendants (hifz al-nasl). These findings confirm that taxes serve not only as an instrument for collecting state revenue, but also as a means of realizing social welfare and justice. This research contributes to the development of tax studies based on Maqasid Syariah and provides implications for the formulation of fairer, more transparent, and more welfare-oriented fiscal policies.